The Truth of Beauty and the Goodness of Chaos: Jim Clarke’s Nietzschean Burgess - Farkas, Ákos (Hungarian Journal of English and American Studies, 2020)
Book review: Clarke, Jim. The Aesthetics of Anthony Burgess: Fire of Words. Cham: Palgrave Macmillan, 2017. xviii + 303 pages. ISBN 978-3-319-66410-1. Hb. £49.29.